An examination of psychological distress and moral injury in journalists exposed to online harassment - Feinstein, Anthony; Storm, Hannah; Mead, Jillian; Sharkey, Andrea (European journal of psychotraumatology, 2025)
Studies show that journalists face repeated, intense online harassment. While data reveal this is distressing to the profession, no detailed psychological study has been undertaken defining what this distress entails. To undertake a descriptive study examining the emotional wellbeing of journalists subject to online harassment. Data from 246 journalists working for a Canadian news organization were collected via a secure study website. Information collected included demographics, harassment metrics (frequency and reasons for harassment); level of organizational support rated on a simple analog scale (0-10, with low scores indicating poor support); psychometric symptoms (anxiety: GAD-7; depression: PHQ-9; posttraumatic stress disorder: PCL-5; moral injury: Toronto Moral Injury Scale for Journalists). The mean age of the sample was 43.07 ( = 11.83) years. Fifty per cent were female. Harassment occurred at least weekly in 65 (26%) of the sample. Anxiety scores in the moderate to severe range were reported by 74 (30.1%) journalists while 34 (13.8%) had PTSD symptoms above the PCL-5 threshold for potential PTSD. Frequency of harassment correlated significantly with anxiety ( = 0.16, = .014), depression ( = 0.15, = .022), PTSD ( = 0.2, = .002) and moral injury ( = 0.3, < .002). Moral injury correlated significantly with anxiety ( = .40), depression ( = .41) and PTSD ( = .44; Spearman's rho, = .001 for all) scores. Organization support was rated as modest ( = 5.80, = 3.01). Frequency of online harassment is associated with a range of emotional responses. While anxiety is the predominant emotion, clinically significant symptoms of PTSD affect a substantial minority of journalists. Moral injury is linked to other indices of emotional distress. News organizations should do more to address the challenges posed by harassment and better support their journalists.